Developing Digital Entrepreneurial Skills among Vocational Students: Evidence from Teaching Factory Based Learning - Puji Fitri Setyaningsih; M Fathur Rahman (Dinamika Pendidikan, 2026)
This research examines the influence of entrepreneurial motivation, digital competence, and self-efficacy, as well as the mediating role of the Teaching Factory, on the development of students’ digital entrepreneurship competencies at SMK Negeri 1 Bawang. Employing an explanatory quantitative research design, a sample of 143 respondents was selected using the Slovin formula, and data were collected through a structured questionnaire. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS 4. The results demonstrate that entrepreneurial motivation, digital competence, and self-efficacy have a positive and significant effect on digital entrepreneurship competencies. Furthermore, the Teaching Factory mediates the relationships between psychological and technical factors and digital-based marketing competencies. These findings suggest that integrating intrinsic motivation, technological literacy, and industry-based learning enhances students’ preparedness for digital entrepreneurship. Theoretically, these results reinforce the competency-based approach in vocational education. Practically, the research offers implications for policymakers in vocational schools to optimize digital-based Teaching Factories by strengthening digital marketing training, utilizing digital business platforms, integrating technology-based business projects, and mentoring sustainable business practices to improve students’ digital entrepreneurship experiences in alignment with the demands of the digital economy.